2011
DOI: 10.1021/ic1021609
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Ion Interaction and Its Effect on Electrostatic Interaction in the System of Copper Chloride and β-Cyclodextrin

Abstract: The present work was devoted to an experimental investigation of the molecule-ion interaction between copper chloride (CuCl(2)) and β-cyclodextrin (CD) and its effect on the electrostatic interaction between Cu(2+) and Cl(-) ions. Our results gave an explicit description of the mutual effect between the interactions. First, the molecular arrangement and surface feature of β-CD experienced a fundamental structural change after interaction with Cu(2+) and Cl(-) ions, which was ascribed to a good separation of Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In a recent work, we prepared a coralline-like macroporous CuCl crystal by sintering a 1 : 1 mixture of copper chloride dihydrate (CuCl 2 •2H 2 O) and b-cyclodextrin (b-CD) 12-17 at 573 K for 2 h in air. 18 This result is unexpected because it has been shown that free CuCl 2 •2H 2 O is sintered to produce anhydrous copper chloride (CuCl 2 , see curve a in Fig. 1) under the same conditions.…”
Section: Introductionmentioning
confidence: 95%
“…In a recent work, we prepared a coralline-like macroporous CuCl crystal by sintering a 1 : 1 mixture of copper chloride dihydrate (CuCl 2 •2H 2 O) and b-cyclodextrin (b-CD) 12-17 at 573 K for 2 h in air. 18 This result is unexpected because it has been shown that free CuCl 2 •2H 2 O is sintered to produce anhydrous copper chloride (CuCl 2 , see curve a in Fig. 1) under the same conditions.…”
Section: Introductionmentioning
confidence: 95%
“…A full description of the applications of b-CDs is given in numerous reviews and papers. [21][22][23][24][25][26] Here, the idea is to take advantage of their unique topologies (rigid structure, large number of hydroxyl groups and ability to form supramolecular adducts with inorganic metal salts) [27][28][29][30] to interact intimately with the metal precursor and control the structure of metal oxide crystallites upon calcination. The strategy has been examined with the synthesis of ZrO 2 , starting from zirconium oxychloride (ZrOCl 2 ?8H 2 O) and 2-hydroxypropyl-b-cyclodextrin (HP-b-CD) as the metal precursor and organic additive, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The interior of β-CD cavity is relatively hydrophobic, whereas the exterior is relatively hydrophilic. 11,12 As a consequence, β-CD, a rigid macrocyclic host, is capable of forming inclusion complexes with many kinds of guests especially hydrophobic guest molecules of appropriate dimensions. [13][14][15][16][17] 18-Crown-6 (18C6) is a flexible macrocyclic polyether capable of forming stable complexes with many salts of the alkali and alkaline earth metals because of its hydrophobic surface and hydrophilic core.…”
Section: Introductionmentioning
confidence: 99%